2015
DOI: 10.2146/ajhp140654
|View full text |Cite
|
Sign up to set email alerts
|

Survey of career satisfaction, lifestyle, and stress levels among pharmacy school faculty

Abstract: A survey of pharmacy faculty in the United States revealed high levels of job satisfaction among respondents, but lower levels of satisfaction with work-life balance and comparable levels of stress to the general population were found. Administrators and stakeholders should explore options to improve lifestyle factors to decrease potential burnout among faculty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 19 publications
2
29
0
9
Order By: Relevance
“…14,19,20 Determining which strategies or combination of strategies that would have the greatest positive impact on work-life balance would be beneficial to explore. Future studies should also focus on what aspects of a pharmacy faculty's career bring satisfaction and which ones bring dissatisfaction in hopes of finding ways to improve work-life balance.…”
Section: Discussionmentioning
confidence: 99%
“…14,19,20 Determining which strategies or combination of strategies that would have the greatest positive impact on work-life balance would be beneficial to explore. Future studies should also focus on what aspects of a pharmacy faculty's career bring satisfaction and which ones bring dissatisfaction in hopes of finding ways to improve work-life balance.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with work satisfaction, success, and productivity include clearly delineated roles and expectations, purposeful use of talents, supportive administration, and collegial community. Incorporating these factors into professional development and mentoring helps faculty members achieve a balance, given that such factors purposefully increase transparency about and culture around responsibilities and expectations 85,94‐96 …”
Section: Part 2: Updates In Faculty Developmentmentioning
confidence: 99%
“…If assessing job satisfaction alone, a work‐life imbalance, which may be contributing to stress, may be missed. Lindfelt et al found high levels of job satisfaction in pharmacy faculty, but this came with lower levels of satisfaction with work‐life balance 95 . The chronic occupational stress to achieve work‐life balance leads to burnout over time.…”
Section: Part 2: Updates In Faculty Developmentmentioning
confidence: 99%
“…Важно отметить, что оценка удовлетворенности карьерой не мо жет приравниваться к удовлетворенности балансом. Так, если удовлетворенность текущей позицией в академии разделяют 86 % сотрудников медицинских факуль тетов, то лишь 37 % отмечают удовлетворенность балансом жизни и труда [Lindfelt et al, 2015]. Более высокий уровень удовлетворенности балансом жизни и труда отмечается среди мужчин [Ip et al, 2018], отражая гендеризированный характер проблематики.…”
Section: формирование аналитической основыunclassified